2023
DOI: 10.11591/eei.v12i3.5006
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis for a suitable propagation model in outdoor with 2.5 GHz band

Abstract: As demand for mobile wireless network services continues to rise, network planning and optimization significantly affect development. One of the critical elements in network planning is predicting pathloss. Thus, propagation models predict pathloss in indoor and outdoor environments. Choosing the appropriate propagation model for the area out of existing models is essential for network planning. Selected propagation models suitable with 2.5GHz, such as Friis Free Space Propagation Model (FSPL), Sandford Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In all three cases there is a greater error in the abscissa axis (mu), affecting the symmetry in the vertical axis. It can be concluded that the logistic distribution is better adapted to the data obtained from radiocommunication systems, which is why the different propagation models are considered as modifications of the logarithmic model [34]. Table 7 presents the distribution correlation matrix for the LQI range parameters of the data set with no missing values.…”
Section: Resultsmentioning
confidence: 99%
“…In all three cases there is a greater error in the abscissa axis (mu), affecting the symmetry in the vertical axis. It can be concluded that the logistic distribution is better adapted to the data obtained from radiocommunication systems, which is why the different propagation models are considered as modifications of the logarithmic model [34]. Table 7 presents the distribution correlation matrix for the LQI range parameters of the data set with no missing values.…”
Section: Resultsmentioning
confidence: 99%
“…By considering the frequency, transmitted distance, height of the base station antenna, and height of the mobile antenna, one could reasonably predict the propagation loss expected in the original Okumura model. However, it should be noted that the calculated losses using the Hata model start to differ from the Okumura curves beyond certain limits [3,6].…”
Section: B Hata Modelmentioning
confidence: 90%
“…Researchers have developed and studied various models that aim to capture the complex characteristics of wireless signals in different propagation environments, such as urban, suburban, and rural areas. These models consider an array of factors, including distance, terrain, building structures, and interference sources, to accurately characterize the wireless channel [3]. The selection of an appropriate radio channel propagation model depends on several factors, including the frequency band, geographical region, and deployment scenario of the wireless network.…”
Section: Radio Wave Propagation Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another paper presented by [72], five different empirical models-the FSPL, SUI model, Ericsson model, Okumura model, and COST-231 Hata model-were compared with empirical data measurements to find the best suitable model to predict path loss in the urban environment of Cologne, Germany, at 2.5 GHz. The analytical results showed that the COST-231 Hata model was the most suitable, with a minimum RMSE of 5.27 dB.…”
Section: Los and Nlos Indoormentioning
confidence: 99%